Proper tools handling for safety worker in oil palm plantation sector / Mohamad Fakhrudin Mohamed - Mohamed, Mohamad Fakhrudin (Faculty of Plantation and Agrotechnology, 2017)
Nowadays, safety of worker is the main issue that have in the oil palm plantation sector. Employees and employers should work together to establish safe working procedures. In this research are to know the affected of the factor which is transportation, store, proper tools handling program and accidental rate to the dependent which is safety worker. The number of population in this study are 300, while the sample size are 150. In this study have two objective which are firstly is to identify the method that can give effect to the safety of worker. The other objective is to identify the dominant factor relate and give impact to the safety of worker. This study do at three estate LKPP Lepar, IOI LeeLau, and Felda Chini 3. The analysis used for this study is the Statistical Package for Science Social (SPSS). In this study the result show that factor transportation, store and proper tools handling program give effect to the safety of worker in oil palm plantation while the factor accidental rate does not give effect or do not have significant to the safety of worker in oil palm plantation sector. The recommendation is all oil palm plantation company need to practices to give their worker proper tools handling program to ensure the safety of their worker and to ensure their worker can handle the tools with a proper ways to reduce risk accidental occur.